Do animal slaughter age and pre-cure freezing have a significant impact on the quality of Iberian dry-cured pork loin?. (September 2021) - Ortiz, Alberto; González, Elena; García-Torres, Susana; Gaspar, Paula; Tejerina, David
Abstract: The influence of various animal slaughter age and of pre-cure freezing times on the quality traits of dry-cured loins from Iberian × Duroc (IBxD) crossbreed animals was assessed. Three animal batches ( n = 15) were selected (IBxD8, IBxD10 and IBxD12) to be slaughtered at the age of 8, 10 and 12 months, respectively. Following slaughter, longissimus thoracis et lumborum muscles were extracted and submitted to curing (T0) or freezing storage during three (T3) or six (T6) months prior to curing. The dry-cured loins from IBxD12 yielded lower intramuscular fat and lightness, a less saturated fatty acid profile and the highest hardness and shear force ( P ≤ 0.05). The pre-cure freezing process increased weight loss, saturated fatty acids, lipid oxidation, and most of the textural parameters ( P ≤ 0.05). So, both slaughter age and pre-cure freezing should be taken into account in order to obtain quality and productive performance. Highlights: Fatty acid profile of dry-cured loins was less saturated with animal age. Pre-cure freezing may compromise dry-cured loin productive performance. Pre-frozen dry-cured loin performance may vary depending on animal slaughter age. Pre-cure freezing impact on lipid oxidation may differ according to animal age. Animal slaughter age and pre-cure freezing increased dry-cured loin hardness.